Enhancing Teacher Competency In Using Technology-Based Interactive Learning Media Through Wordwall Training At Tsanawiyah Dharut Thalibin - Ida Widaningrum; Indah Puji Astuti; Khoiru Nurfitri; Rifqi Rahmatika Az-Zahra; Dyah Mustikasari; Ali Selamat; Bambang Widiyahseno (International Journal Of Community Service, 2024)
This community service focuses on training teachers to use technology-based interactive learning media, especially the Wordwall platform, for Tsanawiyah Dharut Thalibin, Sampung, Ponorogo, and East Java. This training aims to improve teachers' skills in creating interactive digital worksheets to overcome student boredom and increase active participation in learning. The training was carried out in several stages, starting from problem identification and planning to evaluation. The results of this training showed that most teachers had not previously used technology-based learning media. After the training, teachers can use the Wordwall platform to create interactive learning activities, such as quizzes and games, which are expected to increase student engagement and create a more dynamic learning atmosphere. The evaluation showed increased teachers' understanding and skills in interactive learning media.